THE ANALYSIS OF OVERPRESSURE CHARACTERISTIC IN SENORO FIELD, BANGGAI BASIN, CENTRAL SULAWESI - Fachri Mahendra, Muhammad
The study area is located in the Senoro Field, Banggai Basin, Central Sulawesi. The stratigraphy of the Senoro Field consists of Tomori, Matindok, Minahaki, Mentawa, Poh, Kintom, and Biak formations which are Middle Miocene to Recent in age. The purposes of this study are to determine top of overpressure, estimate pore pressure magnitude, analyse overpressure generating mechanisms, and analyse the relationship between geological condition in study area and overpressure. The data processing were performed in five wells (RNR-1, RNR-2, RNR-3, RNR-4, and RNR-5), by using wireline log data, well report, temperature data, pressure data, vitrinite reflectance data, and XRD data. The overpressure characteristic was analyzed by observing pressure/stress profile through depth, wireline log respons through depth, sedimentation rate, sonic log- density log cross plot compared with XRD, and vitrinite reflectance depth plot. Based on data processing and analysis, it is known that some wells show indications of the presence of slight overpressure. The top of overpressure ranges from 2255–3502 ft TVDSS, which is found at shale interval in Kintom Formation. The pore pressure magnitude at the top of overpressure ranges from 1003–1519 psi, and those magnitudes generally increase with increasing depth. The overpressure characterization result shows that the main overpressure generating mechanism in Senoro Field is loading mechanism caused by high sedimentation rate of Kintom Formation, which is ranging from 532-728 m/mY. As an addition, minor overpressure mechanism in forms of hydrocarabon buoyancy contributes to pore pressure increase in the Senoro field. The hydrocarbon buoyancy occurs in Kintom Formation, ranging from 5745-5878 TVDSS, with pore pressure magnitude ranges from 2869-2883 psi.